Association between measures of treatment quality and disease progression in prostate cancer radiotherapy: An exploratory analysis from the TROG 03.04 RADAR trial. Issue 2 (8th December 2017) - Marcello, Marco; Ebert, Martin A; Haworth, Annette; Steigler, Allison; Kennedy, Angel; Bulsara, Max; Kearvell, Rachel; Joseph, David J; Denham, James W
Abstract: Introduction: Quality assurance methods are incorporated into multicentre radiotherapy clinical trials for ensuring consistent application of trial protocol and quantifying treatment uncertainties. The study's purpose was to determine whether post‐treatment disease progression is associated with measures of the quality of radiotherapy treatment. Methods: The TROG 03.04 RADAR trial tested the impact of androgen deprivation on prostate cancer patients receiving dose‐escalated external beam radiation therapy. The trial incorporated a plan‐review process and Level III dosimetric intercomparison at each centre, from which variables suggestive of treatment quality were collected. Kaplan–Meier statistics and Fine and Gray competing risk modelling were employed to test for associations between quality‐related variables and the participant outcome local composite progression. Results: Increased 'dose‐difference' at the prostatic apex and at the anterior rectal wall, between planned and measured dose, was associated with reduced progression. Participants whose treatment plans included clinical target volume (CTV) to planning target volume (PTV) margins exceeding protocol requirements also experienced reduced progression. Other quality‐related variables, including total accrual from participating centres, measures of target coverage and other variations from protocol, were not significantly associated with progression. Conclusions: This analysis has revealed the association of several treatment quality factors with disease progression. Increased dose and dose margin coverage in the prostate region can reduce disease progression. Extensive and rigorous monitoring has helped to maximise treatment quality, reducing the incidence of quality‐indicator outliers, and thus reduce the chance of observing significant associations with progression rates.